Hepatocyte-specific Nrf2 deficiency mitigates high-fat diet-induced hepatic steatosis: Involvement of reduced PPARγ expression - Li, Lu (Redox Biol, 2019)
Non-alcoholic fatty liver disease (NAFLD) is an emerging global disease with increasing prevalence. However, the mechanism of NAFLD development is not fully understood. To elucidate the cell-specific role of nuclear factor erythroid-derived 2-like 2 (NRF2) in the pathogenesis of NAFLD, we utilized hepatocyte- and macrophage-specific Nrf2-knockout [Nrf2(L)-KO and Nrf2(Mϕ)-KO] mice to examine the progress of NAFLD induced by high-fat diet (HFD). Compared to Nrf2-LoxP littermates, Nrf2(L)-KO mice showed less liver enlargement, milder inflammation and less hepatic steatosis after HFD feeding. In contrast, Nrf2(Mϕ)-KO mice displayed no significant difference in HFD-induced hepatic steatosis from Nrf2-LoxP control mice. Mechanistic investigations revealed that Nrf2 deficiency in hepatocytes dampens the expression of peroxisome proliferator-activated receptor γ (PPARγ) and its downstream lipogenic genes in the liver and/or primary hepatocytes induced by HFD and palmitate exposure, respectively. While PPARγ agonists augmented PPARγ expression and its transcriptional activity in primary hepatocytes in a NRF2-dependent manner, forced overexpression of PPARγ1 or γ2 distinctively reversed the decreased expression of their downstream genes fatty acid binding protein 4, lipoprotein lipase and/or fatty acid synthase caused by Nrf2 deficiency. We conclude that NRF2-dependent expression of PPARγ in hepatocytes is a critical initiating process in the development of NAFLD, suggesting that inhibition of NRF2 specifically in hepatocytes may be a valuable approach to prevent the disease.